Deconstructing the Fair-Efficient Dichotomy in Taxpayer Compliance Discourse: Reading Indonesian Tax Policy in the Light of “Laudato Si" - Seralurin, Yohanes Cores; Purwanti, Lilik (Amsir Accounting & Finance Journal, 2026)
This study critically examines the construction of the “fair–efficient” dichotomy in Indonesian tax policy and taxpayer compliance discourse through the lens of Jacques Derrida’s deconstruction and Pope Francis’ Laudato Si’. Although the state frequently frames tax reform as “fair for taxpayers and efficient for the economy,” this research finds that efficiency expressed through fiscal rationality, revenue optimization, and investment competitiveness dominates the discourse, while fairness is reduced to procedural equality and compliance rhetoric. Using a qualitative, critical-interpretive approach, this study analyzes policy texts, official speeches, tax campaigns, and taxpayer narratives to uncover how accounting technologies and digitalization shape the categories of “compliant” and “non-compliant” taxpayers, often marginalizing technologically and structurally vulnerable groups. When viewed from an integral ecology perspective, the findings reveal a significant absence of socio-ecological and intergenerational justice in tax discourse, despite taxation’s central role in resource distribution and environmental governance. This study concludes that tax justice requires a broader normative framework one that not only emphasizes procedural compliance and efficiency but also incorporates ecological responsibility and protection for vulnerable communities. The findings offer theoretical contributions to tax studies and practical implications for more inclusive and ecologically conscious tax policy design